Reflexos da obrigatoriedade da auditoria interna em empresas de capital aberto listadas no novo mercado da B3 - Mussoi, Priscila (Universidade do Vale do Rio dos Sinos, 2024)
This study investigated the consequences of mandatory internal auditing in publicly traded companies listed on B3's Novo Mercado. The research approach was qualitative, in which semi-structured interviews were carried out with 14 professionals responsible for or involved with the internal audit process. Subsequently, the data was processed using Bardin's content analysis. The results showed that, while many companies already had internal audit departments, others were driven to create or adjust their structures due to regulatory requirements. There was a preference for departments with their own teams, but with the need for external expertise in some specific demands, such as information technology and cybersecurity. Furthermore, the requirement for effective investment in the activity was perceived, including supervision by regulatory bodies to distinguish companies that add value from those that merely comply with standards. These findings offer insights into the consequences of mandatory internal auditing in the Novo Mercado, highlighting the importance of considering both regulatory aspects and organizational complexities to guide future practices and research in this area.
Keywords: Auditoria interna; Novo mercado; Obrigatoriedade; B3; Internal audit; New market; Obligatoriness; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis